Antifungal protection by endophytic bacteria in legumes - Valetti, Lucio; Sardo, María Florencia; Posada, Gisella Anabel; Gonzalez, Pablo; Parola, Rodrigo; Paredes, Juan Andrés; Monguillot, Joaquín Humberto; Ruiz, O.A.; Guzzo, María Carla; Monteoliva, Mariela Ines (Sociedade Brasileira de Fisiologia Vegetal (SBFV), 2022)
Poster